Unrooting inequality from development : recognition and justification of inequality in global development - Cisneros Menchaca, Alex (2017)
How does the tension resolve between a moral order with egalitarian imperatives, such as sustainable and inclusive human development, and a global political economy based on a market system that prioritizes meeting the wants and needs of those with purchasing power?